Efficacy of intra-meibomian gland injection of the anti-VEGF agent bevacizumab for the treatment of meibomian gland dysfunction with lid-margin vascularity - Jiang, Xiaodan (Drug Des Devel Ther, 2018)
PURPOSE: To investigate the efficacy of a novel treatment – intra-meibomian gland (MG) injection of the anti-VEGF agent bevacizumab – for MG dysfunction (MGD) with eyelid-margin vascularity. METHODS: A total of 26 eyes from 13 patients diagnosed with MGD and eyelid-margin vascularity were included in our study. Patients received intra-meibomian gland injections of bevacizumab (150 μL, 2.5 mg/0.1 mL) at multiple sites with a 29 G needle where telangiectasia was severe. The Ocular Surface Disease Index (OSDI), tear film, tear-breakup time (TBUT), eyelid-margin features, MG features, conjunctiva, and corneal staining were assessed at 1 day before injection and 1 week, 1 month, and 3 months after injection. Blood pressure, best-corrected visual acuity, intraocular pressure, and slit lamp examinations were performed to assure the safety of patients at 1 day before and 1 day, 1 week, 1 month, and 3 months after injection. RESULTS: Lid-margin vascularity, conjunctival injection, expressed secretion quality, expressivity of the MG, TBUT, corneal staining, and OSDI were significantly improved 1 week, 1 month, and 3 months after injection compared to baseline values. Lid-margin vascularity, conjunctival injection, meibomian gland expressivity, TBUT, and OSDI continued to improve; the greatest improvements were observed at 1 month and sustained for 3 months. Spearman’s correlation analysis indicated that age and sex significantly influenced TBUT improvement. Females and older patients tended to have shorter baseline TBUT that followed a different trend from that of males and younger patients during postinjection visits, revealed by subgroup analysis. No local or systemic side effects were observed at follow-up visits. CONCLUSION: This study is the first to explore a novel therapy for MGD – intra-MG injection of the anti-VEGF agent bevacizumab – and it demonstrates that the treatment is effective and safe in eliminating eyelid-margin vascularity, improving MG function and relieving clinical signs and symptoms of MGD.